2006
DOI: 10.1539/joh.48.20
|View full text |Cite
|
Sign up to set email alerts
|

Methanol‐Induced Oxidative Stress in Rat Lymphoid Organs

Abstract: Methanol-Induced Oxidative Stress in Rat Ly m p h o i d O r g a n s : N a r a y a n a p e r u m a l J . PARTHASARATHY, et al. Immunology Laboratory, Department of Physiology, Dr. ALM. PG. Institute of Basic Medical Sciences, University of Madras, Taramani Campus, India-Methanol is primarily metabolized by oxidation to formaldehyde and then to formate. These processes are accompanied by formation of superoxide anion and hydrogen peroxide. This paper reports data on the effect of methanol on antioxidant status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 43 publications
14
52
0
Order By: Relevance
“…Then ACTH acts on adrenal gland to release corticosterone secretion. Parthasarathy et al (2006) reported a similar increase in plasma corticosterone level in rats after methanol administration for day 1 and 15 days. However after 30 days of methanol intoxication it showed considerable decrease in corticosterone level.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Then ACTH acts on adrenal gland to release corticosterone secretion. Parthasarathy et al (2006) reported a similar increase in plasma corticosterone level in rats after methanol administration for day 1 and 15 days. However after 30 days of methanol intoxication it showed considerable decrease in corticosterone level.…”
Section: Discussionmentioning
confidence: 57%
“…This alteration after aspartame administration may be attributed to its metabolite methanol. Methanol is primarily metabolized by oxidation to formaldehyde and then to formate, these processes are accompanied by the formation of superoxide anion and hydrogen peroxide (Parthasarathy et al, 2006). Oxidative damage in a cell or tissue occurs when the concentration of reactive oxygen species (O 2 -, H 2 O 2 , and OH -) generated exceeds the antioxidant capability of the cell (Sies, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in glutathione level observed in our study may be attributed to methanol release from aspartame, this is due to methanol metabolism depends upon glutathione (Parthasarathy et al, 2006). The reduction of reduced glutathione, elevation of oxidized GSSG and decrease of the reduced/oxidized ratio increase cell sensitivity to oxidative stress (Shelly et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…It was reported that methanol is primarily oxidized to formaldehyde and then into formate, that is involved in methanol toxicity in human. This is accompanied by production of superoxide anion and hydrogen peroxide (Lee et al, 1994, Eells et al, 2000, Parthasarathy et al, 2006.There are a few data showed the effect of aspartame consumption on specific neurological conditions such as headache, insomnia and seizures (Johns, 1986), alterations in regional concentrations of catecholamine which is accompanied with behavioral disturbances (Coulombe andSharma, 1986, Humphries et al, 2008). The rational of this study was to investigate whether long-term uses of aspartame can affect oxidative stress and brain neurotransmitters in albino rats…”
Section: Introductionmentioning
confidence: 99%